Ultra-old patients and long-term survival after hip fracture: a real-world assessment - Tiso, Debora; Pizzonia, Monica; Giannotti, Chiara; Tagliafico, Luca; Signori, Alessio; Nencioni, Alessio; Monacelli, Fiammetta (Frontiers in Medicine, 2023)
It’s still undetermined whether ultra persons aged >90 years ( ultra old) are able to tolerate hip fracture surgical stress, maintaining their functional reserve and even fewer evidence has investigated the role of frailty on the risk of mortality, disability or morbidity in the ultra-old . This is a prospective study performed at the Orthogeriatrics ward of IRCCS Policlinico San Martino, Hospital (Genoa, Italy), that consecutively enrolled 205 old age patients with hip fractures due to low-energy trauma. Namely, 85 patients were ultra old and 120 patients (64-89 years) were considered the younger control group. Demographic data, perioperative data and rehabilitation were collected.Here we estimated the overall survival and the associated predictive variables in hospitalized ultra-old hip fractured patients based on a methodologically robust frailty stratification ( Rockwood 40 items). The median OS for ultra-old was 18.7 months and, similarly, they showed a double fold 1 year mortality risk. Our findings assessed that frailty in presence of malnutrition, delayed verticalization and post- operative respiratory complications were associated with a double-fold risk increase for long-term mortality, irrespective of advanced chronological age in ultra old.Although the higher mortality rate in those patients may be related to a priori lower life expectancy, chronological age alone is a insufficient prognostic determinant for unfavourable outcomes. Our multicomponent prognostic score may be apply in combination to frailty stratification to ultra-old to timely screen for and deliver goals of care discussions prior to surgery, targeting potentially new orthogeriatric pathways for the improvement of appropriateness and treatment intensity.